Final Evolution and Delayed Explosions of Spinning White Dwarfs in Single Degenerate Models for Type Ia Supernovae - Benvenuto, Omar Gustavo (2015)
We study the occurrence of delayed SNe~Ia in the single degenerate (SD) scenario. We assume that a massive carbon-oxygen (CO) white dwarf (WD) accretes matter coming from a companion star, making it to spin at the critical rate. We assume uniform rotation due to magnetic field coupling. The carbon ignition mass for non-rotating WDs is MigNR ≈ 1.38 M⊙; while for the case of uniformly rotating WDs it is a few percent larger (MigR ≈ 1.43 M⊙). When accretion rate decreases, the WD begins to lose angular momentum, shrinks, and spins up; however, it does not overflow its critical rotation rate, avoiding mass shedding. Thus, angular momentum losses can lead the CO WD interior to compression and carbon ignition, which would induce an SN~Ia. The delay, largely due to the angular momentum losses timescale, may be large enough to allow the companion star to evolve to a He WD, becoming undetectable at the moment of explosion. This scenario supports the occurrence of delayed SNe Ia if the final CO WD mass is 1.38 M⊙ < M < 1.43 M⊙. We also find that if the delay is longer than ~3 Gyr, the WD would become too cold to explode, rather undergoing collapse.